Economic And Poverty Indicators In Indonesia: A Simulation of The Impact of Rice Price Changes - Banyu Sunarya, Iqbal (Coopetition : Jurnal Ilmiah Manajemen, 2025)
This study aims at analyzing the impact of rice price increase on poverty reduction and income inequalities indicators. Using National Socio-Economic Survey data and simulation with Indonesian Input-Output table, it was revealed that the increasing rice price has lowered the output of 174 out of 185 industrial sector listed on the input-output table including rice milling sector, agriculture sector, fertilizer sector and other related sectors. In terms of supply, rice price increase leads to the declining payment on capital and labor production factor, while in terms of demand, it decreases consumption rate and import so that generally it results in the declining economic output (GDP). Partially and isolated from other policies, rice price increase has contributed to the increasing poverty line but it reduces the inequality among the poor. As rice price rises, the poverty line also rises. Due to the fixed income level, the poverty rate increases. From the producer perspective, rice price increase provides additional income for rice farmers (or at least it does not increase their expenditure) that are largely made up of the rural poor society. On the other hand, in terms of the consumer, the increase in rice prices increases the level of expenditure or lowers their real income level (since rice is the staple food). Because both are moving in the opposite direction (approaching), the level of income inequality among the poor becomes lower.